FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERTUMBUHAN BAYI 6-12 BULAN DI PUSKESMAS SIMPANG BARU - Herlina, Sara (Jurnal Endurance, 2018)
Growth can also be defined as increasing size and number of cells in all parts of the body that can be quantitatively measured, such as height, weight, and head circumference. Growth is very closely related to the nutritional status of children. Riskesdass results from 2007 to 2013 show an alarming fact that underweight increased from 18.4% to 19.6%, stunting also increased from 36.8% to 37.2%, while wasting decreased from 13.6 % to 12.1%. This study aims to determine the factors associated with baby growth. The design of this study was cross sectional with a large sample of 151 people. Sampling method used systematically random sampling. The data were analyzed by univariate, bivariate and multivariate. The results obtained normal growth as many as 90 people (59.6%). The results of multivariate analysis of variables related to infant growth were inclusive ASI Pvalue 0,002 (OR: 3,324), maternal knowledge Pvalue <0,000  (OR: 3.912), maternal occupations Pvalue 0,037 (OR: 2,311). The conclusions in this study are factors related to infant growth of 6-12 months in Puskesmas Simpang Baru is exclusive breastfeeding, mother knowledge, and mother jo.  It is recommended that health workers need to conduct counseling, counseling, especially pregnant women on the importance of exclusive breastfeeding and the impact on infant growth. There should also be a support group of ASI in the community. Pertumbuhan dapat juga diartikan sebagai bertambahnya ukuran dan jumlah sel di seluruh bagian tubuh yang secara kuantitatif dapat diukur, seperti tinggi badan, berat badan, dan lingkar kepala. Pertumbuhan sangat erat kaitannya dengan pemberian ASI eksklusif karena ASI merupakan makanan terbaik untuk bayi dan mengandung antibodi sehingga bayi jarang sakit. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan pertumbuhan bayi. Desain penelitian ini adalah cross sectional dengan besar sampel 151 orang. Metode sampling yang digunakan systematis random sampling. Analisis data dilakukan secara univariat, bivariat dan multivariat. Hasil penelitian diperoleh pertumbuhan normal sebanyak 90 orang (59,6%). Hasil analisis multivariat variabel yang berhubungan dengan pertumbuhan bayi adalah variabel ASI esklusif Pvalue 0,002 (OR: 3,324), pengetahuan ibu Pvalue <0,000   (OR: 3,912), pekerjaan ibu Pvalue 0,037  (OR: 2,311). Kesimpulan pada penelitian ini adalah faktor-faktor yang berhubungan dengan pertumbuhan bayi 6-12 bulan di Puskesmas Simpang Baru adalah ASI Eksklusif, pengetahuan ibu, dan pekerjaan ibu. ASI eksklusif dan dampak terhadap pertumbuhan bayi. Perlu juga dibentuk kelompok pendukung ASI dimasyarakat.